A guided reading of images: a strategy to develop critical thinking and communicative skills - Sarmiento Sierra, Marisol (Colombian Applied Linguistics Journal, 2010)
This article describes the effects of a strategy aimed at helping students develop critical thinking and communicative skills by means of a program for guided reading of images using the questioning technique in an EFL context. Many teachers are not prepared for the education of critical thinkers as part of their curricular work. This is a qualitative descriptive research study carried out with third graders from a public school in Bogotá, Colombia in which field notes, artifacts, and questionnaires were used as data collection instruments. The study showed that the program activated children’s mental processes to allow them to move from basic to higher levels of critical thinking while communicating their thoughts in Spanish as well as using vocabulary in English. This strategy could be used by teachers of different disciplines.